Peran Corporate Social Responsibility dalam Meningkatkan Daya Saing Perusahaan Global: Sebuah Studi Literatur - Suhailah, Roshikah Wafa; Anggraini, Wulan; Rahmat, Hayatul Khairul; Efendi, Azil Akbar; Wulandari, Desi (Journal of Current Research in Management, Policy, and Social Studies, 2025)
Corporate Social Responsibility (CSR) has become a crucial factor in the business strategies of global companies. This study aims to examine the role of CSR in enhancing corporate competitiveness in the global market through an analysis of relevant literature. By examining the implementation of CSR in various multinational companies, this study demonstrates that CSR is not merely a moral obligation but also a strategy that can enhance reputation, customer loyalty, and operational efficiency. Effective CSR implementation can strengthen stakeholder relationships, mitigate reputational risk, and expand markets through social and environmental sustainability. This article concludes that CSR is a strategic element in enhancing corporate competitiveness, especially in an increasingly competitive global market.